Index for the appropriate vancomycin dosing in premature neonates and infants. Issue 1 (22nd November 2021) - Endo, Aiju; Nemoto, Atsushi; Hanawa, Kazumi; Ishikawa, Takahiro; Koshiishi, Mai; Maebayashi, Yuki; Hasebe, Yohei; Naito, Atsushi; Kobayashi, Yoshifumi; Isobe, Katsuhiko; Kawano, Yayoi; Hanawa, Takehisa
Abstract: Background: In neonates, vancomycin (VCM) is used to treat Gram‐positive bacterial infections. However, VCM blood concentrations are affected by gestational age, bodyweight (BW), and renal function. The initial VCM dose adjustment can therefore be difficult, and few reports have evaluated this issue. In this study, we investigated the factors determining the appropriate VCM dosing schedule in neonates, especially premature infants. Methods: The VCM dosage and trough concentrations were retrospectively investigated from the initial treatment to maintenance therapy in neonatal intensive care unit patients who underwent therapeutic drug monitoring. We examined the average single‐administration VCM dosage during maintenance therapy. We then compared the actual VCM dose with that calculated using an index comprising six items that influence the VCM daily dose (postnatal age, gestational age, BW, serum creatinine level, urine output, and lactate level). Results: Twenty premature infants were included. The average BW of patients at the initial VCM administration was 975 g. During maintenance therapy, the average VCM dose was 8.4 mg/kg, and the median trough concentration was 12.4 μg/mL. When we applied the six‐item index, 18 of 20 patients (90%) had concordant results between the actual VCM dosing schedule and the VCM calculated using the index. Conclusions: The average VCM dose and six‐item index can facilitate the transition from the initial VCM dose to an appropriate dose in many cases and contribute to early treatment in low‐birthweight infants with more variable BW, distribution volumes, and renal function. In conclusion, our six‐item index may help standardize VCM administration in premature infants.